STUDY ON CREATIVE ECONOMY ACTIVITY CHARACTERISTICS AND INNOVATIONS IN CREATIVE ECONOMY DEVELOPMENT IN URBAN KAMPONG - Desri Kumala Dewi, Endar
Urban kampong are part of a urban settlement as a physical, social, and economical system that functions as residence, workplace, and a place of socialisation that is physically affected by the physical condition of the environment as well as other resources. As an economic system, urban kampong is a place for the community to do productive activities (home-based enterprises) as well as a support to the city economic activities. One of the developing economic activities in urban kampong is the screen printing and convection industry at Kampung Sablon Suci which has been going on for around 30 years. This research aims to identify the creative economic activity characteristics developing in urban kampong that involves production, marketing, institutional support, as well as innovations done in business development. The analytical methods used in this paper is descriptive statistical analysis and content analysis. Descriptive statistical analysis is used to get an overview of the production, marketing, and innovation activities undertaken by enterpreneurs. Content analysis is used to identify programs, activities, and institutional support for the development of creative economy as well as conditions that support the development of creative economy activities at the urban kampong. Research findings indicate that creative economy development in urban kampong possess great benefits and potential. With its informal characteristics, creative economy activities in urban kampong is capable in sustaining the economics of the residents by using local resources, eradicating unemployment as well as accommodating work force that couldn’t make it in the formal sector. Based on analysis results, conditions that support creative economy activities include ease of obtaining raw materials, employer capacity, marketing reach, competitiveness of the products, support from business, as well as innovation from entrepreneurs. Overall, the supporting conditions are conditions in production, marketing, and innovation done by the entrepreneurs. Based on those three things, it can be concluded that the development of creative economy activities still relies and is dominated by the entrepreneurs. Entrepreneurs have roles as creative actors and innovators. In the early stages, the process of transferring creative knowledge and technical skills are done through internships that are taught past from family generations or self-taught from activity observation. In the next stage of development, entrepreneurs independently defend and develop creative economic activities through production, marketing, and innovation. Entrepreneurs are the main actors as the source of creative human xi resources that is capable of production, accessing markets, and create innovations as one of the main dynamic keys in the creative economy development at the urban kampong. In the development process, entrepreneurs is capable of creating incremental innovation that include products, process, and marketing using technology and existing production equipment in a gradual and continuous manner. In the aspect of institutional support, support from external parties, particularly the local government, intellectual bodies and communities aren’t optimal yet. Regulations as well as the proactive role from the local government is still very much needed to support the creative economic activities development in urban kampong. This is due to the mismatch between the obstacles faced by the entrepreneurs and the programs held by the local government. The local government is expected to be more proactive, increasing the intensity of program socialisation as well as optimizing the programs and activity inside the urban kampong as the focus of creative economic environment in accordance to the needs of the entrepreneurs.